Expanding Medical Education and Task Shifting; Comment on "Doctor Retention: A Cross-sectional Study of How Ireland Has Been Losing the Battle" - Daniel R. Arnold (Kerman University of Medical Sciences, 2021)
Brugha et al provide convincing evidence that Ireland stills need to overcome many hurdles, including poor training and working experiences in Irish hospitals, before it can significantly improve its record on doctor retention. The findings reported by Brugha et al are particularly disappointing in light of the fact that Ireland implemented a doctor retention strategy in early 2015. Ultimately, doctor retention is important because it can help alleviate the health workforce shortages that many countries face currently and that are projected to worsen over the next decade. The purpose of this commentary is to highlight two additional strategies for alleviating health workforce shortages - expanding medical education and task shifting.